Community-Based Collaborative Management in Central Sulawesi Grand Forest Park - Nur Azizah; Golar; Sudirman Daeng Massiri; Imran Rachman; Andi Sahri Alam (Agricultural Science, 2026)
Community-based collaborative management is increasingly adopted in conservation governance. However, previous studies have examined Collaborative Governance and Co-Management separately, providing limited understanding of how collaborative processes and authority-sharing interact in state-managed conservation areas. This study analyzed community-based collaborative management in Central Sulawesi Forest Park by integrating both perspectives. A descriptive qualitative case study involved 23 purposively selected informants representing government, Forest Farmer Groups, village governments, local communities, and civil society organizations. Data were collected through interviews, observations, questionnaires, and document analysis, analyzed using an interactive qualitative approach, and validated through source and method triangulation. Across eight analytical dimensions, collaborative governance facilitated stakeholder dialogue, institutional arrangements, facilitative leadership, and community participation, while co-management was reflected in shared management responsibilities, access to conservation benefits, and social learning. However, strategic authority remained with government under the legal framework for conservation management, whereas communities primarily performed operational roles. Community-based collaborative management has been effectively implemented through complementary governance rather than equal decision-making authority. This study integrates Collaborative Governance and Co-Management into a unified analytical framework and provides a context-specific interpretation of shared authority, showing that authority sharing in state-managed conservation areas is achieved through complementary roles, with governments retaining strategic authority and communities undertaking substantial operational responsibilities.